High Temperature Sensitivity Pressure Sensors Based on Filter Paper as a Mold. Issue 14 (1st January 2019) - Yang, Congcong; Maimaitiyiming, Xieraili; Mi, Hongyu
Abstract : As an item commonly used in daily life, filter paper could be used as a mold to easily produce sensitive, efficient, stable and commercially valuable pressure sensors. The PDMS film prepared by the filter paper mold is completely coated by SWCNTs and encapsulated by a polyethylene (PE) film to obtain a high temperature sensitivity pressure sensors (TSPS). The TSPS is sensitive between 0 Pa and 0.84 kPa pressure ranges, it is sensitivity reached at 29.94 KPa −1 . The TSPS had high sensitivity for identifying low pressures (33.4 × 10 −6  N), and long-lasting stability over 5, 500 pressure dynamic cycles. In addition, sensors made by this method can measure temperature changes under static pressure. TSPS has good temperature sensing performance, which showed sensitivity of 0.277%/°C under 261.8 Pa pressure and 0.251%/°C under 1231.8 Pa pressure. Pressure and temperature sensors have been successfully applied to a variety of real life scenarios, which indicates that they have the potential to be applied to human life.